Host-cell-assisted construction of a folate-engineered nanocarrier based on viral light particles for targeted cancer therapy. Issue 42 (21st October 2021) - Lv, Cheng; Ao, Jian; Wang, Ji; Tang, Man; Liu, An-An; Pang, Dai-Wen
Abstract : A universal artificial nanocarrier is constructed via the host-cell-assisted modification of multifunctional viral light particles with folate, which enhances the tumor-targeting ability for targeted cancer therapy. Abstract : Targeted cancer therapy has aroused the broad interest of researchers due to its accuracy in specific tumor targeting and its few side effects on normal cells. In the last decades, oncolytic viral light particles (L-particles) have been transformed into smart nanocarriers for targeted drug delivery. However, these L-particles, similar to the oncolytic viruses that they are derived from, can only recognize tumor cells expressing corresponding receptors, severely limiting their universal application. Although modification of targeting agents onto their envelope can overcome this limitation, it is still a great challenge to do so without interfering with their biofunction since the envelope is fragile. Herein, a host-cell-assisted strategy is proposed to construct folate-engineered nanocarriers (F-L-particles) with their biofunctions maintained to the largest extent. The F-L-particles were further multi-functionalized by encapsulating ultrasmall near-infrared quantum dots and antitumor drugs in them for tumor real-time imaging and therapy. Such a moderate, efficient and convenient cell-based strategy facilitates the development and widespread application of these bio-nanocarriers in the field of targeted cancer therapy, and drives the interdisciplinary studies of nanotechnology, chemistry, and virology.